2021
DOI: 10.3390/ijms22031140
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Nonspecific Alkaline Phosphatase Function in Bone and Muscle Progenitor Cells: Control of Mitochondrial Respiration and ATP Production

Abstract: Tissue nonspecific alkaline phosphatase (TNAP/Alpl) is associated with cell stemness; however, the function of TNAP in mesenchymal progenitor cells remains largely unknown. In this study, we aimed to establish an essential role for TNAP in bone and muscle progenitor cells. We investigated the impact of TNAP deficiency on bone formation, mineralization, and differentiation of bone marrow stromal cells. We also pursued studies of proliferation, mitochondrial function and ATP levels in TNAP deficient bone and mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Recent studies have shown that TNSALP may have a regulatory role in bone and muscle progenitor cells influencing musculoskeletal health. Thus, low levels of this enzyme have been associated with muscle weakness and diminished motor coordination [ 51 ]. Additionally, it has been revealed that TNSALP can modulate mitochondrial function and ATP levels, and defects in it can be associated with mitochondrial dysfunction, cell respiration, and increased reactive oxygen species, leading to metabolic disturbances in this population [ 51 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that TNSALP may have a regulatory role in bone and muscle progenitor cells influencing musculoskeletal health. Thus, low levels of this enzyme have been associated with muscle weakness and diminished motor coordination [ 51 ]. Additionally, it has been revealed that TNSALP can modulate mitochondrial function and ATP levels, and defects in it can be associated with mitochondrial dysfunction, cell respiration, and increased reactive oxygen species, leading to metabolic disturbances in this population [ 51 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Thus, low levels of this enzyme have been associated with muscle weakness and diminished motor coordination [ 51 ]. Additionally, it has been revealed that TNSALP can modulate mitochondrial function and ATP levels, and defects in it can be associated with mitochondrial dysfunction, cell respiration, and increased reactive oxygen species, leading to metabolic disturbances in this population [ 51 ]. The different manifestations can be classified from the most severe to the mildest forms in perinatal lethal hypophosphatasia, infantile hypophosphatasia, childhood-onset hypophosphatasia, adult hypophosphatasia, odontohypophosphatasia, and benign perinatal hypophosphatasia [ 8 , 21 , 26 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Published data however report data difficult to reconcile, maybe relying on the different maturation stage of cells used in these studies. It was for instance shown that bone marrow stromal cells from Alpl −/− or Alpl +/− mice or from patients with hypophosphatasia generate more adipocytes than bone marrow stromal cells from corresponding controls [ 92 , 93 , 94 ], suggesting that TNAP prevents MSC commitment toward adipocytes. On the other hand, Esteve et al, reported that TNAP was particularly expressed in a subpopulation of beige adipocyte progenitors, where its chemical or molecular inhibition reduced the levels of markers associated with adipocyte differentiation (PPARγ2, ChREBP, UCP1, LPL), and decreased TG accumulation [ 95 ].…”
Section: Pathophysiological Tnap’s Function In Adipocytesmentioning
confidence: 99%
“…To our knowledge, TNAP lacks classical mitochondrial addressing signals. Interestingly, an article published in this issue reports that TNAP is also likely associated with mitochondria in bone and muscle progenitor cells [ 94 ]. In these cells, TNAP inhibition increased mitochondrial respiration and ATP production [ 94 ], providing molecular evidence to understand why TNAP-deficient mice, sheep and humans have mitochondria with disorganized cristae and/or reduced muscle strength [ 15 , 94 , 103 ].…”
Section: Pathophysiological Tnap’s Function In Adipocytesmentioning
confidence: 99%
See 1 more Smart Citation